An experimental investigation on FPZ evolution of concrete at different low temperatures by means of 3D-DIC. (August 2020) - Fan, Bing; Qiao, Yanmin; Hu, Shaowei
Highlights: 3D-DIC was applied to investigate the FPZ evolution of concrete at low temperatures. The opening displacements and the crack profiles at different loading points were obtained. The effect of temperature on the crack propagation was analyzed. The FPZ evolution during fracture process of concrete at different temperatures was presented. Abstract: The three-point bending tests of concrete specimens at different temperature levels (20 ℃, 0 ℃, −20 ℃, and −40 ℃) were performed using a low-temperature fracture test system. The 3D digital image correlation (3D-DIC) technique was employed to measure the surface deformations of the beams during fracture process. Combined with the displacement fields obtained from 3D-DIC, the crack propagation lengths and crack widths at different loading points were determined, providing information for the fracture process zone (FPZ) evolution in concrete at different temperatures. The results revealed that temperature has significant effect on the crack propagation, i.e. the average FPZ length in the later stage of unloading and the critical crack length ac decrease with decreasing temperature. In addition, the FPZ length for specimens at 0 ℃, −20 ℃ and −40 ℃ decreases slowly in the initial stage and then decreases significantly when the crack extends to the specimen boundary.